Arthroscopic removal of an osteoid osteoma of the acetabulum - Barnhard, Renske (Springer-Verlag, 2011)
In this case report, we describe the arthroscopic removal of an osteoid osteoma from the acetabulum in a young adolescent. After identifying the osteoid osteoma close to the cartilage with MRI and CT investigations, we decided that in this case, arthroscopic removal was the best treatment. In the case of an osteoid osteoma in the acetabulum close to the cartilage, arthroscopic removal should be considered as one can treat the associated osteochondritic lesion during this procedure. Level of evidence IV.